Anti-corruption policies in Asia and the Pacific : (Asian Development Bank, 2006)
This book includes many parts: preventing corruption in public administrations, the political sphere, and the business sector, sanctioning and prosecuting corruption and related offences, involving the public in the fight against corruption.